Integrasi Chatbot Berbasis GPT Terhadap Website E-Commerce (Studi Kasus Toko JSA) - Made Putra Teguh Pramana; I Gede Surya Rahayuda (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2023)
A website is a series of sites with related hyperlinks that individual, organization, company, or government made. E-commerce websites are websites that have features for transaction through online services. Toko jsa emas perak is one of the companies that want to develop its company’s presence on the internet using e-commerce websites. uniqueness is important to have an edge between online competition. By implementing chatbot system in the e-commerce websites it can increase the effect on user in each interaction. the propose of this research is to implement a chatbot service in the toko jsa websites.